Structural elucidation of [Cu2(p-H2NC6H4COO)3(CH3(CH2)14COO)(H2O)(NH3)]/ Ahmad Nazeer Che Mat and Mohamad Isa Mohamadin - Che Mat, Ahmad Nazeer; Mohamadin, Mohamad Isa (2023)
A novel copper (II) mixed carboxylates namely bis(p-aminobenzoato)bis(hexadecanoato)dicopper(II), [Cu2(p-H2NC6H4COO)3(CH3(CH2)14COO)(H2O)(NH3)], from one-pot self-assembly of the corresponding ions was designed to function as a low-temperature and thermally-stable metallomesogen applications. The asprepared copper (II) complex was characterized by means of elemtal analyses, FTIR and UV-Vis spectroscopy for the determination of its elemental compositions, chemical bonding, and electronic transition, respectively. FTIR analysis indicate the presence of all expected functional group with ΔCOO value were 106 cm-1 and 194 cm-1, suggesting the binding mode of carboxylate ligands at Copper(II) centre are chelating and bridging (monoatomic, syn-anti), respectively. Complex 1 exhibit square pyramidal geometry around Copper(II) as indicated by UV-Vis spectroscopy in solid state condition. Meanwile, dissolution of Complex 1 in DMSO:CH3COOH lead to the structural reorganization into producing symmetrical mononuclear complex (D2h symmetry) and an unsymmetrical mononuclear complex (C1 symmetry).